Students’ Performance in Arranging English Words into Simple Sentences Utilizing Jumbled-Word Cards - Juhansar; Prasetyoaji, Ari; Pabbajah, Mustaqim; Mahardika, Nia Arba (Center of Language and Cultural Studies [CLCS], 2022)
In the modern era, teachers can use jumbled words as a medium in the learning-teaching process, especially in English. This research aims to discover the students' performance in arranging simple sentences utilizing jumbled-word cards. This research relays on quantitative descriptive research. The respondents of this research are the eight-grade students of MTs Al Kautsar Sleman in the academic year 2021/2022. The researchers select one class as the respondents, consisting of 15 (fifteen) students. The students were taught by applying a jumbled-words technique. The instrument for collecting data was a test. After collecting data, the researchers analyzed students’ performance by measuring the grammatical aspect of the test results. The test is about simple present tense and present continuous tense. This research shows that 10 (ten) students’ have 8 (eight) scores and 5 (five) students have 7 (seven) scores. Both are categorized in the